Status of Quality in Strategic Purchasing in the Health System: A Systematic Review - Zarei, Zahra (2020)
Introducction. Strategic purchasing is an important component of financing in the health system. It can enhance productivity, justice, and accountability in the health care delivery in case of considering the quality. This study, which was conducted as a systematic review, was aimed at investigating the status of quality in five domains of strategic purchasing in the health system to answer what, for whom, from whom, how to buy, and how much to buy. Material and Methods: This study systematically reviewed the articles published in the databases of Web of Sciences (WOS), Scopus, PubMed, Medline via Ovid, Embase from 2000 to October 2019. The keywords used to search the databases included the following: Health Care Sector, Delivery of Health Care, Quality Assurance, Quality Improvement, and Strategic Purchasing. A total of 182 articles were selected and reviewed by four researchers. Articles with irrelevant content were excluded. Data of the selected articles were analyzed using the content analysis method. Results: Of the 182 articles collected through searching the selected databases, 16 articles were analyzed. Based on the results of this study, strategic purchasing in the health system results in the delivery of services with higher quality. Conclusion: Strategic purchasing can enhance the performance of the health system through choosing the most appropriate provider and the most appropriate payment method, along with equity in providing quality health care services.